Perancangan Baru Perpustakaan Rekreatif Tingkat Provinsi Jawa Barat Dengan Pendekatan Teknologi - Muhamad Adnan, Fadhli; Nur Sheha Gunawan, Ahmad; Primiana, Arnanti (eProceedings of Art & Design, 2024)
Libraries are important facilities for storing, maintaining and using collections of books and other library materials. Apart from its educational function, libraries have also developed into recreational facilities. Indonesian people's interest in visiting libraries, although relatively low, has increased significantly in recent years. In Bandung, the number of library visits will increase by 27% in 2023, supported by several factors such as modern library designs and diverse facilities. Community activities in libraries have also developed not just as a place to read books but also as a social and recreational facility. So the design of a recreational library building needs to be considered. Seeing the trend of technology integration in library systems and facilities, this recreational library needs to be designed by applying technology applications to its interior while still taking into consideration not to leave behind the essence of the meaning of the library itself. The aim of this design is to create a new technology-based recreational library design in the city of Bandung. To increase public interest in visiting libraries with strategic locations, an area that is known as a tourist destination, namely Cihampelas or Ciwalk Bandung, was chosen as the location for the new design. Keywords: library, technology, recreation